2008
DOI: 10.1007/s11356-008-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure of pharmaceuticals and musk fragrances in the Somes River before and after upgrading the municipal wastewater treatment plant Cluj-Napoca, Romania

Abstract: Background, aim, and scope Pharmaceutically active substances are a class of emerging contaminants, which has led to increasing concern about potential environmental risks. After excretion, substantial amounts of unchanged pharmaceuticals and their metabolites are discharged into domestic wastewaters. The absence of data on the environmental exposure in Eastern Europe is significant, since use patterns and volumes differ from country to country. In Romania, the majority of wastewater, from highly populated cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The results obtained for CARB and CLF AC agree with their already stated high recalcitrance to biodegradation and photodegradation in surface waters, conventional activated sludge WWTPs and polishing ponds (Heberer 2002;Hijosa-Valsero et al 2010;Matamoros and Salvadó 2012;Moldovan et al 2009;Tixier et al 2003). Finally, the greater elimination of CARB (71 ± 4 % in 2 days) in reactors planted with Lemna sp.…”
Section: Poorly Degradable Compoundssupporting
confidence: 89%
“…The results obtained for CARB and CLF AC agree with their already stated high recalcitrance to biodegradation and photodegradation in surface waters, conventional activated sludge WWTPs and polishing ponds (Heberer 2002;Hijosa-Valsero et al 2010;Matamoros and Salvadó 2012;Moldovan et al 2009;Tixier et al 2003). Finally, the greater elimination of CARB (71 ± 4 % in 2 days) in reactors planted with Lemna sp.…”
Section: Poorly Degradable Compoundssupporting
confidence: 89%
“…The combination of widespread use and incomplete WWTP elimination results into an extensive occurrence of IBP in surface waters. Indeed, this compound has been detected in water systems all over the word (Zuccato et al, 2005;Zhao et al, 2009;Yu et al, 2009;Pailler et al, 2009;Moldovan et al, 2009;Fernandez et al, 2010;Camacho-Munoz et al, 2010;Loos et al, 2010;Teijon et al, 2010;Zhao et al, 2010;Helenkar et al, 2010;Waiser et al, 2011;Wang et al, 2011;Lewandowski et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial decrease in these compounds in the Somes River was observed due to the upgrade of the municipal WWTP in Cluj-Napoca as seen in Fig. 2 [34]. Cyclophosphamide and pentoxyfylline could not be detected, while the concentrations and loads of caffeine decreased by one order of magnitude after the upgrade of the WWTP Cluj-Napoca.…”
Section: Types Of Edcs/ppcpsmentioning
confidence: 92%
“…The Somes river (Romania), receives a variety of organic wastes from urban areas, factories and individual households, as well treated and nearly untreated wastewater effluents from several municipal wastewater treatment plants (WWTPs), among which the WWTP of the city Cluj-Napoca is the largest. It was observed that the concentrations of the pollutants varied strongly along the river course between the cities Cluj-Napoca and Dej as follows: caffeine: 230 -9700 ng/L, carbamazepine: 30 -70 ng/L, galaxolide: 10 -310 ng/L and ibuprofen: 30 -120 ng/L [34]. A substantial decrease in these compounds in the Somes River was observed due to the upgrade of the municipal WWTP in Cluj-Napoca as seen in Fig.…”
Section: Types Of Edcs/ppcpsmentioning
confidence: 99%